Segmental English Phonemes In NF’s Rap Song Story: Exploring Type And Rule - Abdullah, Bachtiar; Mahmud, Lida Holida (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
This study aims to identify phonemes’ changing in NF rap song, in terms of the types of phonological rules in vowels and consonants; assimilation, dissimilation, and deletion. Furthermore, this study figures out how these phonological rules are formed. The rap song Story NF is chosen as the object study in terms of research on phoneme analysis in rap song is still limited. This research applied a qualitative approach. This research employs Lass' (1984) theory as the main theory to analyze data. The data found fifty cases which consist of six regressive assimilation, nine progressive assimilation, four fusional assimilation, two dissimilation, and thirty-three deletion processes. They consist of twenty-two aphaeresis, four syncope, and seven apocope. The findings show that progressive assimilation is the most frequently applied process from the assimilation aspect. At the same time, aphaeresis is the most commonly used process in the deletion aspect, highlighting how connected speech is naturally formed to adapt to the rhythm-driven nature of rap music. All of this connected speech occurs because of rapid speech.